Exploring the Role Performance of Corporate Ethics Officers - Adobor, Henry (Journal of business ethics, 2006)
Organizations continue to show renewed focus on managing their ethics programs by developing organizational infrastructures to support their ethics implementation efforts. An important part of this process has been the creation of an ethics officer position. Whether individuals appointed to the position are successful in the role or not may depend on a number of factors. This study presents a suggested framework for their effectiveness. The framework includes a focus on personal, organizational and situational factors to predict performance in the role. The study examines the complex nature of the role. These include task complexity, low task visibility, role conflict, and role ambiguity. Personal, organizational and situational factors that can serve as buffers against the complexities associated with the role are presented. The study suggests that individuals with certain competencies and orientations may be better suitable for the ethics position, and firms need to consider key organizational and situational issues critical to the performance of an ethics officer. The research and practice implications of the study are given.